DEVELOPMENT AND SHELTER CHALLENGES OF SMALL ISLANDS: PLANNING WITH A PRO-POOR PERSPECTIVE - Ashok Das (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2018)
This paper explores why and how small island developing states (SIDS) in the Asia-Pacific region should adopt pro-poor policies to overcome development related affordable housing challenges. It first outlines SIDS’ common development challenges—small size, remoteness, greater exposure to economic and environmental shocks, and brisk urbanization. In a globalized world, SIDS’ developmental and geographic constraints make providing equitable shelter harder. Developing Asia’s rapid urban growth and simultaneously widening urban inequality offer hope and sound caution alike for SIDS, whose potential and propensity to attract global investment are unique. Tourism-based economic development is poised to accelerate the private sector’s influence on SIDS’ land and housing markets. This paper presents the cities of Honolulu (USA), Surabaya (Indonesia), and Dili (Timor Leste) as cases that exemplify, respectively, the advanced, intermediate, and early stages of a possible development continuum for SIDS. Utilizing secondary literature, primary qualitative field-research, news media sources, and observations, it demonstrates that despite common developmental challenges SIDS’ diverse governance models and institutional capacities preclude definitive solutions. Instead, it argues for tailored yet flexible policy responses informed by multiple pro-poor principles—inclusivity, affordability, alternative forms of tenure security, and innovative design and construction. Sensitive, context-appropriate adaptation of innovative policy tools that have proven effective in fraught contexts elsewhere (especially, transfer of development rights, inclusionary housing, land pooling/sharing, participatory slum upgrading, and community benefits agreements) can guide SIDS to expand pro-poor shelter provision.